Two fluorescence turn-on coumarin Schiff's base chemosensors for cyanide anions. (March 2016) - Wang, Kangnan; Ma, Lin; Liu, Guoqun; Cao, Duxia; Guan, Ruifang; Liu, Zhiqiang
Abstract: Two novel diethylaminecoumarin Schiff's base chemosensors for cyanide with pyridine or thiophene as terminal group have been synthesized. Their photophysical properties as well as recognition properties for cyanide anions have also been examined. Both the compounds exhibit strong green fluorescence in all the solvents. Density functional theory calculation indicates that both the compounds exhibit intramolecular charge transfer from diethylaminecoumarin group to terminal pyridine or thiophene group. The compounds can recognize cyanide anions with fluorescence turn-on response based on copper ion complex displacement mechanism and obvious color change from red to yellow-green can be observed by naked eyes. The chemosensors exhibit a degree of repeatability and can be used repeatedly to recognize cyanide anions for several times. Graphical abstract: Highlights: Two new coumarin Schiff's base chemosensors for CN − have been synthesized. The compounds can recognize CN − with fluorescence turn-on response. The chemosensors exhibit good repeatability. The compounds recognize CN − based on copper ion complex displacement mechanism.